(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of integrating visual components into the speech recognition process for improving robustness has been identified by recent developments in audio visual emotion recognition (AVER). Visual characteristics have a strong potential to boost the accuracy of current techniques for speech recognition and have become increasingly important when modelling speech recognizers. CNN is very good to work with images. An audio file can be converted into image file like a spectrogram with good frequency to extract hidden knowledge. This paper provides a method for emotional expression recognition using Spectrograms and CNN-2D. Spectrograms formed from the signals of speech it’s a CNN-2D input. The proposed model, which consists of three layers of CNN and those are convolution layers, pooling layers and fully connected layers extract discriminatory characteristics from the representations of spectrograms and for the seven feelings, performance estimates. This article compares the output with the existing SER using audio files and CNN. The accuracy is improved by 6.5% when CNN-2D is used.